Dora the explorer Movie Theater : storybook & movie projector - Koeppel, Ruth.; Mangano, Tom (Pleasantville, NY : Reader's Digest Children's Books, 2007)
Contains four stories in which Dora the Explorer and Boots help Daisy, baby jaguar, la Maestra, and Woo Hoo the explorer star; and includes a DVD with an episode of the television program as well as interactive games.
2.4
K-3
DVD.
K-3.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Dora the Explorer (Fictitious character) -- Fiction; Dora the Explorer (Fictional character) -- Fiction; Radio and television novels; DVDs; Radio and television novels; DVD-Video discs